Protocol for a pilot randomised, double-blind, placebo-controlled trial for assessing the feasibility and efficacy of faecal microbiota transplantation in adolescents with refractory irritable bowel syndrome: FAIS Trial - Max Nieuwdorp; Judith Zeevenhooven; Clara Marieke Andrea de Bruijn; Arine Vlieger; Marc Alexander Benninga (BMJ Paediatrics Open)
Background Irritable bowel syndrome (IBS) is a common chronic medical condition, in both children and adults. Despite the availability of effective (non)pharmacological treatments, symptoms persist in a significant amount of patients with IBS. Faecal microbiota transplantation (FMT) may be an effective alternative treatment in adolescents with refractory IBS through manipulation of the intestinal microbiota.Methods and analysis This randomised, placebo-controlled single-centre pilot study will assess feasibility and efficacy of FMT in 30 adolescents (16–21 years) with refractory IBS. Patients will be randomly allocated (1:1) to receive two allogeneic (healthy donor) or two autologous (own) faecal infusions at baseline and after 6 weeks. Primary outcomes will assess feasibility, including patient and donor recruitment, adherence and incidence rates of adverse events. To evaluate clinical efficacy, secondary outcomes will include the proportion of patients with at least >50% reduction of their abdominal pain intensity and frequency 12 weeks after the first FMT, and after 6-month and 12-month follow-up. Other outcomes comprise changes in faecal gut microbiota composition, quality of life, depression and anxiety, school or work absenteeism and adequate relief, measured directly after FMTs and after 6 and 12 months of follow-up.Discussion This randomised controlled trial will investigate the feasibility and effectiveness of repetitive FMTs in adolescents with refractory IBS.Ethics and dissemination The study is approved by the Medical Research Ethics Committees AMC (MEC-AMC) in the Netherlands.Trial registration number NCT03074227.